COMPARATIVE STUDIES OF CONSTITUTIONAL COURTS: THE ROLE OF ABSTRACT JUDICIAL REVIEW AND CONSENSUALISM IN DECISIONAL PROCESS AND IN DEMOCRATIC STABILITY - Tomio, Fabricio Ricardo de Limas; Robl Filho, Ilton Norberto; Kanayama, Rodrigo Luís (Revista Jurídica (FURB), 2018)
Spain and Portugal created the Constitutional Courts and the two biggest Latin American federations (Brazil and Mexico) forged or expanded the abstract judicial review in their Supreme Courts in the 1980’s and 1990’s, which were the democratic consolidation decades. Despite the similarities among these countries, the degree of influence on the decisional process (the relationship between government and parliaments, and parliamentary minorities and parliamentary majorities) are not identical, as is the degree of political consensualism. In this sense, the central questions are: How effective is the abstract judicial review in decisional process? What are the differences? Do the Constitutional Courts or Supreme Cortes interfere and cancel the decisions of the other branches and political institutions with no distinction or prejudice or they support the decisions of the majority? How autonomous are the Courts and their decisions? Is the abstract judicial review an important ingredient to democracy stability, to decisions capabilities of the government and majorities and to institutional consensualism? The Law and the Political Science achieved a degree of knowledge about the participation of Courts in the decisional process. However, the comparative studies about Latin American and Iberian Courts, which use empirical data, are rare. Therefore, the aim is to determine the role of the abstract judicial review on democratic consolidation and in the decisional capability of all these countries. The research presents, in a comparative view: 1) Ações Diretas de Inconstitucionalidade, in Brazil (5.457 lawsuits, 1988-2016); 2) Acciónes de Inconstitucionalidad, in Mexico (1.146 lawsuits, 1994/2015); 3) Recursos de Inconstitucionalidad, in Spain (643 lawsuits, 1980-2016); and, 4) Fiscalização Sucessiva, in Portugal (563 lawsuits, 1983-2016). Those four types of actions are capable to realize the abstract judicial review. To understand the impacts of the abstract judicial review, the methodology of the analysis will be: (i) institutional variables (the actors, different types of lawsuits, the procedure to nominate judges, etc.), (ii) politics variables (composition of the parliament/government, coalitions, decision stability, nomination of judges, government or parliamentary majority opinion on unconstitutionality/constitutionality of the law). The studies, specifically, analyses the empirical validity of this hypothesis: if the Courts do not decide countermajorities or against the rights and interests of the central government. The preliminary conclusions of the data analysis indicate empirical validity on this hypothesis in Brazil, Mexico and Spain, but not in Portugal.